Deformation Analysis of Electric SUV Crash Box: Comparison Between Hollow and 3D-Printed Lattice Core Models Using ANSYS Explicit Dynamics - Moh. Ahnaf Aqil; Ferly Isnomo Abdi; Sudirman Rizki Ariyanto; Diah Wulandari (CV. Creative Tugu Pena, 2025)
The development of SUV electric vehicles requires a crash box system that is able to reduce deformation more effectively than conventional hollow designs that tend to be unstable when subjected to high-energy impacts. This study compared the performance of three crash box models, namely hollow, lattice 3D-printed core, and lattice with internal divider wall using ANSYS Explicit Dynamics simulation. The main parameters analyzed include the folding pattern of collapse and maximum deformation as indicators of structural stability. The simulation results showed that all models were in concertina deformation mode, but the stability levels differed significantly. The crash box hollow recorded the largest deformation of 47,579 mm, while the divider-less lattice model decreased to 38,899 mm. The lattice configuration with divider walls is the most superior design with a minimum deformation of 31,098 mm, as well as a more symmetrical and controlled fold pattern. These findings confirm that the integration of the lattice structure, especially with the internal divider is capable of increasing rigidity and inhibiting axial buckling without significant mass gain. Further research is recommended evaluating lattice topology variations and experimental tests as verification of numerical results.